2016
DOI: 10.1128/aem.00455-16
|View full text |Cite
|
Sign up to set email alerts
|

The apt /6-Methylpurine Counterselection System and Its Applications in Genetic Studies of the Hyperthermophilic Archaeon Sulfolobus islandicus

Abstract: Sulfolobus islandicus serves as a model for studying archaeal biology as well as linking novel biology to evolutionary ecology using functional population genomics. In the present study, we developed a new counterselectable genetic marker in S. islandicus to expand the genetic toolbox for this species. We show that resistance to the purine analog 6-methylpurine (6-MP) in S. islandicus M.16.4 is due to the inactivation of a putative adenine phosphoribosyltransferase encoded by M164_0158 (apt). The application o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1
1

Relationship

3
6

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 53 publications
0
15
0
Order By: Relevance
“…Two exceptions, topR2 ( M164_1245 ) and apt ( M164_0158 ), were identified to have significant growth defects on plates once they were knocked out (Supplementary Fig. 1c, 2a and 20 ), likely resulting in their under-representation in our transposon library. The third, cdvB3 ( M164_1510 ), a paralog of cdvB , may be incorrectly called essential in our Tn-seq analysis.…”
Section: Resultsmentioning
confidence: 99%
“…Two exceptions, topR2 ( M164_1245 ) and apt ( M164_0158 ), were identified to have significant growth defects on plates once they were knocked out (Supplementary Fig. 1c, 2a and 20 ), likely resulting in their under-representation in our transposon library. The third, cdvB3 ( M164_1510 ), a paralog of cdvB , may be incorrectly called essential in our Tn-seq analysis.…”
Section: Resultsmentioning
confidence: 99%
“…Based on the lethal incorporation of 6-methylpurine in the purine salvage pathway through TK0664 expression, the TK0664/6-MP system has allowed the deletion of multiple genes in different archaea [ 23 , 45 ]. In this study, we demonstrated the relevance of using this counterselection marker in T. barophilus .…”
Section: Discussionmentioning
confidence: 99%
“…Homologous recombination (via double-crossover events) efficiencies using linear DNA have been reported in three hyperthermophilic archaea: Thermococcus kodakarensis KOD1, 10 2 colonies/ μ g linear DNA containing 1 kb flanking regions [ 22 ]; P. furiosus COM1 (parent strain DSM 3638), 2.9 × 10 3 colonies/ μ g linear DNA containing 1 kb flanking regions [ 21 ]; S. islandicus M.16.4, 20–30 colonies/ μ g linearized DNA (pC-SsoargD) containing 755 and 671 bp flanking regions [ 10 ] and 10–50 colonies/ μ g linearized DNA (pMID-apt) containing 703 and 617 bp flanking regions [ 23 ]; and S. islandicus REY15A, 10–200 colonies/ μ g linearized DNA (pKL2) containing 1.5 kb flanking regions [ 2 ]. The homologous recombination efficiency reported in our current study (10 2 -10 3 colonies/ μ g DNA) was higher than that of T. kodakarensis and S. islandicus and nearly identical to that of P. furiosus .…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, the genetic marker system developed in this study will allow versatile genetic manipulation in S. acidocaldarius . Notably, a higher concentration of agmatine was required for cultivation of the S. acidocaldarius argD -deficient strain when compared with other hyperthermophiles [ 10 , 20 , 23 , 28 ].…”
Section: Discussionmentioning
confidence: 99%